Calamatic azobenzine liquid crystal series: synthesis and mesomorphic properties of 1-methoxyalkyloxy-4'-(4-phenylazo)acetophenone - Salisu, Abdulsalam Abubakar; Ab. Rahman, Mohamad Zaki; Silong, Sidik; Rahman, Lutfor; Ahmad @ Ayob, Mansor (Asian Network for Scientific Information, 2009)
New series of calamitic liquid crystal materials with rod-shape azobenzene moieties as a core has been synthesized and characterized by spectroscopic methods. The mesomorphic properties were investigated by differential scanning colorimetry, polarizing optical microscopy and X-ray diffraction. The rod-shaped molecule 1-methoxyalkyloxy-4`-(4-phenylazo)acetophenone was prepared by diazotization of 4-Aminoacetophenone, coupling with phenol and subsequent etherification of 1-bromoalkyloxy-4`-(4-phenylazo)acetophenone in methanol. The presence of smectic A mesophases was confirmed by the textures and X-ray diffraction studies. Compounds 4a-4d (C3-C6) exhibits enantiotropic smectic A phase while, compound 4d (C8) show monotropic smectic A phase.